AN ANALYSIS OF THE NATURE OF SCIENCE TO DEVELOP SCIENTIFIC LITERACY SKILLS IN GRADE 5 STUDENTS ON THEME 3 SUB-THEME 1 MATERIALS - Rahmaniati, Rita; Aulia, Nadiatul; Saprina, Putri Devi; Sayyidana, Zahra Ahla (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2026)
Science learning in elementary schools has been using student textbooks based on the 2013 curriculum revised in 2017. Is the essence of science already present in each subject? This study analyzes the science textbooks used by students daily, in accordance with the objectives of science learning, which include products, processes, and attitudes, so that science learning objectives are optimally achieved. The qualitative research method was conducted through content analysis. Data analysis techniques included data reduction, presentation, and conclusion drawing. The results indicate that the essence of science as a product, process skill, and attitude has not yet been fully discovered. The essence of science as a product is limited to facts, concepts, and principles/laws. Meanwhile, other aspects can still be developed. The essence of science as a process also only includes several process skills: observing, classifying, concluding, and communicating. Two aspects remain undiscovered: measuring and predicting. The essence of science as an attitude in the textbook is more comprehensive because it includes: honesty, openness to new ideas, responsibility, objectivity, cooperation, critical thinking, curiosity, self-awareness, discipline, and concern for the environment. The nature of science in science learning in elementary schools will have an impact on students' ability to think logically, analytically, be able to solve authentic problems and be able to apply scientific attitudes in everyday life.